2014
DOI: 10.1093/icesjms/fsu191
|View full text |Cite
|
Sign up to set email alerts
|

A major nursery area around the Svalbard archipelago provides recruits for the stocks in both Greenland halibut management areas in the Northeast Atlantic

Abstract: Greenland halibut in the Northeast Atlantic currently have two separate management units: the Northeast Arctic (NEA) stock and the West Nordic (WN) stock. The biological basis for this separation is weak, and while the NEA stock has a well-described nursery area in the waters around the Svalbard archipelago, no such major nursery area is known for the WN stock. To examine the linkages between these two stocks, a tagging experiment was conducted in the Svalbard nursery area, which is the only known large nurser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
(30 reference statements)
4
22
0
Order By: Relevance
“…Our results are consistent with previous studies (Fairbairn 1981;Riget et al 1992;Knutsen et al 2007;Albert and Vollen 2015), but most of these studies do not cover the wide geographic range of the species. Both Knutsen et al (2007) and Roy et al (2014) found significant genetic differences between samples across the barrier we detected.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results are consistent with previous studies (Fairbairn 1981;Riget et al 1992;Knutsen et al 2007;Albert and Vollen 2015), but most of these studies do not cover the wide geographic range of the species. Both Knutsen et al (2007) and Roy et al (2014) found significant genetic differences between samples across the barrier we detected.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence of isolation by distance was found across the Atlantic, both calculated along the major currents and shortest marine distance. This subdivision of the Greenland halibut across the Atlantic has been suggested in earlier studies (Fairbairn 1981;Riget et al 1992;Knutsen et al 2007;Albert and Vollen 2015) and is corroborated by a recent morphometric comparison of otoliths from South Greenland and Norway, respectively (Harbitz and Albert 2015). No evidence for subdivision of Greenland halibut was found either within the western Atlantic (south and west of Iceland) or within the eastern Atlantic (north and east of Iceland).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, given that black scabbardfish and deep-water sharks apparently spatially overlap, other management measures should be introduced [109]. In contrast, many ray and skate species are usually taken as target species and bycatch in demersal fisheries for flatfish with thornback ray (Raja clavata) and thorny skate (Amblyraja radiata) accounting for 90-95% of the total skate bycatch in the North Sea and in the Barents Sea ecoregions, respectively [113,114]. In the North West Atlantic, sharks and their relatives are generally taken in direct fisheries and also incidentally captured, mainly in USA, Canada and Mexico (Atlantic side), and with less extent in Caribbean waters [16,115,116].…”
Section: Chondrichthyes Bycatch In the North Atlantic And Potential Smentioning
confidence: 99%